Using linked administrative, clinical and primary data to explore the impact of and factors associated with non-adherence to in-hospital medication changes in 30-days post hospital discharge. (2018) - Weir, Daniala; Motulsky, Aude; Lee, Todd; Abrahamowicz, Michal; Morgan, Steve; Buckeridge, David; Tamblyn, Robyn
No abstract available